Formal method to implement fuzzy requirements (2012)
Many user requirements may involve preference criteria linguistically expressed by fuzzy terms in natural language; these requirements are called fuzzy requirements. Database query languages have been extended incorporating fuzzy logic to handle user-preference criteria. To the best of our knowledge, very few of the software development methods consider fuzzy queries. In this work, we propose a database application method which includes conversion rules that translate formal specifications to implementations in the structured query language (SQL) enhanced with fuzzy logic (SQLf). The novelty of our method is the tuple calculus extension in order to express fuzzy queries with formal specification. Also, our method includes conversion rules that translate formal specifications into implementations in SQLf, a fuzzy query language on crisp databases. Additionally, we illustrate how our method was successfully applied in a real case study.